2008
DOI: 10.1123/apaq.25.2.132
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peer Tutoring on Interaction Behaviors in Inclusive Physical Education

Abstract: This study assessed the effect of peer tutoring on physical, instructional, and social interaction behaviors between elementary school age students with severe and multiple disabilities (SMD) and peers without disabilities. Additional measures addressed the activity time of students with SMD. The study was conducted in inclusive general physical education settings under three instructional support conditions for students with SMD: (a) teacher-directed, (b) peer-mediated, and (c) voluntary peer support. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
3
16

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 38 publications
4
82
3
16
Order By: Relevance
“…One study showed an increase in interaction among students with significant disabilities and their peers following peer training in how to provide coaching to students with disabilities (Klavina & Block, 2008). Other researchers suggest that children with significant disabilities in school settings may need a continuum of options to participate in physical activity, including specialized settings, reverse inclusion, and full inclusion (Block, Taliaferro, & Moran, 2013).…”
Section: Physical Activity Interventionsmentioning
confidence: 99%
“…One study showed an increase in interaction among students with significant disabilities and their peers following peer training in how to provide coaching to students with disabilities (Klavina & Block, 2008). Other researchers suggest that children with significant disabilities in school settings may need a continuum of options to participate in physical activity, including specialized settings, reverse inclusion, and full inclusion (Block, Taliaferro, & Moran, 2013).…”
Section: Physical Activity Interventionsmentioning
confidence: 99%
“…Cooperative learning has proliferated in inclusive education for different academic purposes (Klavina et al, 2014). Besides fostering students" agency and cooperation, it increases interactions between peers with and without disabilities (Klavina and Block, 2008).…”
Section: Pérez-parreño and Padilla-petry 189mentioning
confidence: 99%
“…A presente revisão sistemática selecionou quatro artigos, [20][21][22][23] os quais apresentaram resultados relacionados sobre a tutoria em alunos com deficiência nas aulas de educação física. Através destes achados, podemos observar a escassez de publicações nacionais sobre esta temática, visto que todos os estudos selecionados são internacionais, dos quais três estudos são procedentes dos Estados Unidos e um da Suécia.…”
Section: Desenvolvimentounclassified
“…21 Neste estudo foi avaliado o efeito da tutoria sobre os comportamentos físico, instrucional e de interação social entre estudantes da escola primária com deficiências múltiplas e seus pares sem deficiências em aulas de educação física, em três condições de ensino: dirigida pelo professor, mediada de", que trata-se de uma versão particular da tutoria entre pares, onde a classe inteira de alunos está envolvida na função reciproca de tutor e tutorado. Os demais artigos utilizaram-se da tutoria aos pares, onde os tutores são definidos através de critérios pré estabelecidos, sempre sendo participantes da mesma aula de educação física dos alunos com deficiência.…”
Section: Desenvolvimentounclassified